2001
DOI: 10.1016/s0002-9440(10)64073-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome-Scale Analysis of Gene Expression Profiles in T Cell Lymphoma Cells during Malignant Progression Using a Complementary DNA Microarray

Abstract: Using a cDNA microarray, we compared the expression of approximately 8000 genes between two unique, clonally related T cell lines derived from different stages of a progressive T cell lymphoma involving skin. A total of 180 genes was found to be differentially expressed at the RNA level by a factor of fivefold or greater. Cutaneous T cell lymphoma is the most common lymphoproliferative disorder involving skin. It usually is an indolent, low-grade tumor at the time of presentation. Over time, the CTCL often und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 38 publications
2
28
0
1
Order By: Relevance
“…These cells are representative of the primary tumors and retain the features of the original lymphoma. 26 All 3 PCALCL cells highly expressed SATB1, and Mac-2A and -2B cells showed significantly higher expression ( Figure 1C), whereas the other CD30…”
Section: Statisticsmentioning
confidence: 96%
“…These cells are representative of the primary tumors and retain the features of the original lymphoma. 26 All 3 PCALCL cells highly expressed SATB1, and Mac-2A and -2B cells showed significantly higher expression ( Figure 1C), whereas the other CD30…”
Section: Statisticsmentioning
confidence: 96%
“…Analysis of several B-NHLs series has led to the definition of molecular subgroups with specific outcomes (Alizadeh et al, 2000;Rosenwald et al, 2002;Shipp et al, 2002;Thieblemont et al, 2004). In contrast, only a limited number of T-cell neoplasms have been investigated using microarrays, including mycosis fungoides (Tracey et al, 2003), leukemic phase of cutaneous T-NHL (Kari et al, 2003), cell lines derived from T-cell malignancies (Li et al, 2001;Fillmore et al, 2002), or PTCL (Martinez-Delgado et al, 2004). A recent profiling analysis was focused on the comparison between PTCL and T-lymphoblastic lymphoma (T-LBL) types (Martinez-Delgado et al, 2004), but a molecular classification of PTCL entities has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 This approach has now been used successfully by a number of groups to identify distinct gene expression patterns in various tumors, tumor cell lines, and disease states. [17][18][19][20][21][22][23][24] In this study, we use cDNA microarrays to examine the global transcriptional profiles of four t(14;18)-positive lymphoma-derived cell lines and demonstrate that they can be readily distinguished from two t(11;14)-positive mantle-cell lymphoma cell lines on the basis of their respective expression profiles. We also demonstrate the utility of real-time quantitative fluorescence RT-PCR for validation of microarray expression data and show how this approach may be used to identify differentially expressed genes that could be involved in the development of t(14;18)-positive NHLs.…”
mentioning
confidence: 99%